2013
DOI: 10.2298/abs1303037n
|View full text |Cite
|
Sign up to set email alerts
|

Models of the potential distribution and habitat preferences of the genus Pipiza (Syrphidae: Diptera) on the Balkan peninsula

Abstract: Seven species of the genus Pipiza, collected throughout the southern and western Balkans, were used for the analysis of habitat preferences and potential geographical distribution on the Balkan Peninsula. The analyzed species show a wide and uneven distribution across the delineated geographical-biogeographical regions. The highest number of species noted is from two regions - the Dinaric mountain chain and the Pannonian and subpannonian regions (seven and six). Land cover patch analysis revealed that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Additionally, temperature can act indirectly by affecting phenology, abundance and quality of visiting plants that are food resource for adults, as well as for aphids that are larval prey. Although Nikolić et al [50] concluded that most of the Pipiza species prefer forests habitats, our results showed that climate would have the most influential impact on their distribution. Moreover, climate change could fundamentally alter the composition, structure, and biogeography of forests in many regions [92].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Additionally, temperature can act indirectly by affecting phenology, abundance and quality of visiting plants that are food resource for adults, as well as for aphids that are larval prey. Although Nikolić et al [50] concluded that most of the Pipiza species prefer forests habitats, our results showed that climate would have the most influential impact on their distribution. Moreover, climate change could fundamentally alter the composition, structure, and biogeography of forests in many regions [92].…”
Section: Discussioncontrasting
confidence: 85%
“…The most recent comprehensive revision of Pipiza taxonomy based on both morphological and molecular evidence resolved 12 European species [49]. However, the ecology and factors shaping the distributions of these hoverflies remains largely understudied [50]. It is known that preferred habitats of Pipiza species mostly include forest, forest edges, tall herbs and shrubs along tracks and in open areas, whereas the predaceous larvae feed on gall-forming aphids on foliage ([51] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the 40-70% likelihood rates of the predictive model in this area instead of percentages close to 100. The degree of coincidence between predictive models and reality could increase if we use other variables that consider the connection of hoverflies with flowering plants and their preference for open or closed areas, like plant type and its coverage percentage or land use [68,69]. As an example, fungus genera employed in our potential distribution analysis have been proved to be very effective to make the model stronger and more accurate, as the expected distribution of the studied species of Cheilosia largely coincided with those of the fungi studied.…”
Section: The Implication Of Potential Distributions In Forthcomingmentioning
confidence: 99%